Law - Evans, Virginia; Dooley, Jenny; Smith, David J. (Berkshire Express Publishing, 2018)
Career Paths: Law is a new educational resource for business professionals who want to improve their English communication skills in a work environment. Incorporating career-specific vocabulary and contexts, each unit offers step-by-step instruction that immerses students in the four key language components: reading, listening, speaking and writing. Career Paths: Law presents subject matter including basic legal concepts, court processes, legal billing, evidence, and international law.
Keywords: Luật học